A preliminary investigation of digital media supplements for head and neck anatomy: Does production format matter?. Issue 6 (14th May 2022) - Willett, Gilbert M.; Forbes, Anna; Spagna, James; O'Kane, Barbara; Weston, Michael; Jergenson, Margaret; Norton, Neil S.
Abstract: From cassettes to digital, use of video in education has evolved. Supplemental digital media is a common educational adjunct within gross anatomy courses. As these aids have advanced technologically, so has production cost. Traditional lecture (T‐lect) productions tend to be more efficient. Traditional gross anatomy laboratory (T‐lab) productions requiring cadaver dissection and high‐definition video are comparatively less efficient. This preliminary study pragmatically assessed T‐lect and T‐lab supplemental learning tools in a head and neck anatomy course for first‐year dental students. Two videos of similar length were developed for different anatomical regions. Learning objectives were similar while format differed. A carotid triangle supplement was created using a T‐lab production format and an infratemporal fossa aid was created using a T‐lect format. Both incorporated recommended elements for facilitating learning. Development time and costs were documented. Student exam performance on topic specific questions was collected along with survey data. Group mean exam score comparisons between students who viewed ( n  = 74 T‐lect, n  = 70 T‐lab) versus did not view ( n  = 27 T‐lect, n  = 30 T‐lab) each aid revealed higher scores for the "viewed" group. The T‐lab production cost ($15, 190 versus $10, 003) and time (19 hr. versus 18 hr) were greater than T‐lect. Descriptive survey data did not reveal a format preference. Students valued previews/summaries and structure highlighting/labeling within the supplements. Students appreciated the supplemental learning aids and mean exam scores were higher for users. Since production format did not noticeably alter exam performance and satisfaction was similar, production efficiency should take precedence.